A LITERATURE REVIEW STUDY ON HR POLICIES AND PRACTICES FOR GEN Z EMPLOYEES: INSIGHTS FROM THE IT/ITES SECTOR - Sharma, Chandani; Abraham, Sheena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The sudden influx of Generation Z (Gen Z) into the workforce has demanded the organizations, especially in the IT/ITES sector, to alter their human resources (HR) policies according to their added expectations of work, which this generation shaped through technology and driven by purpose. The present study examines HR management practices in the light of Gen Z work preferences, AI applications in HR processes, and importance of sustainable HRM practices for employee engagement and retention. Methods employed included an extensive literature review of 72 peer-reviewed articles and studies covering topics of HR policy, AI-based HRM, and sustainability in workforce management. The analysis classifies the findings worthy of consideration into three broad themes: (1) HR policies and work expectations of Gen Z, (2) AI and digital HRM practices, and (3) sustainability-driven HRM methods. The results indicate that Gen Z employees value flexibility, career development, meaningful work, and well-being, forcing organizations to reconsider traditional HR frameworks. AI can help with recruitment, performance management, and online learning, thereby improving the employee experience and efficiency. Nevertheless, there are still issues of data privacy, digital fatigue, and AI ethics. Green HRM and CSR are becoming leading factors for attracting and retaining Gen Z workers as sustainability and ethical employment practices contribute greatly to job satisfaction and the organization’s commitment over time. In conclusion, organizations shall devise a way to interlink personalized HR policies, AI talent management, and sustainability-oriented HRM measures to meaningfully engage, retain, and empower Gen Z employees. Future research should evaluate the application of AI tools for HR, engage with localized trends of Gen Z workforce, and understand long-term effects of sustainability-led HR strategies upon the organizations under IT/ITES.